Postoperative interventions for preventing bladder dysfunction after radical hysterectomy in women with early‐stage cervical cancer - Aue-aungkul, Apiwat (Cochrane Database Syst Rev, 2021)
BACKGROUND: Bladder dysfunction is a common complication following radical hysterectomy, caused by the damage to pelvic autonomic nerves that innervate the muscles of the bladder, urethral sphincter, and pelvic floor fasciae. Bladder dysfunction increases the rates of urinary tract infection, hospital visits or admission, and patient dissatisfaction. In addition, bladder dysfunction can also negatively impact patient quality of life (QoL). Several postoperative interventions have been proposed to prevent bladder dysfunction following radical hysterectomy. To our knowledge, there has been no systematic review evaluating the effectiveness and safety of these interventions for preventing bladder dysfunction following radical hysterectomy in women with cervical cancer. OBJECTIVES: To evaluate the effectiveness and safety of postoperative interventions for preventing bladder dysfunction following radical hysterectomy in women with early‐stage cervical cancer (stage IA2 to IIA2). SEARCH METHODS: We searched the Cochrane Central Register of Controlled Trials (CENTRAL; 2020, Issue 4) in the Cochrane Library, MEDLINE via Ovid (1946 to April week 2, 2020), and Embase via Ovid (1980 to 2020, week 16). We also checked registers of clinical trials, grey literature, conference reports, and citation lists of included studies. SELECTION CRITERIA: We included randomised controlled trials (RCTs) evaluating the effectiveness and safety of any type of postoperative interventions for preventing bladder dysfunction following a radical hysterectomy in women with stage IA2 to IIA2 cervical cancer. DATA COLLECTION AND ANALYSIS: Two review authors independently selected potentially relevant RCTs, extracted data, assessed risk of bias, compared results, and made judgments on the quality and certainty of the evidence. We resolved any disagreements through discussion or consultation with a third review author. Outcomes of interest consisted of spontaneous voiding recovery one week after the operation, quality of life (QoL), adverse events, post‐void residual urine volume one month after the operation, urinary tract infection over the one month following the operation, and subjective urinary symptoms. MAIN RESULTS: We identified 1464 records as a result of the search (excluding duplicates). Of the 20 records that potentially met the review criteria, we included five reports of four studies. Most of the studies had unclear risks of selection and reporting biases. Of the four studies, one compared bethanechol versus placebo and three studies compared suprapubic catheterisation with intermittent self‐catheterisation. We identified two ongoing studies. Bethanechol versus placebo The study reported no information on the rate of spontaneous voiding recovery at one week following the operation, QoL, adverse events, urinary tract infection in the first month after surgery, and subjective urinary symptoms for this comparison. The volume of post‐void residual urine, assessed at one month after surgery, among women receiving bethanechol was lower than those in the placebo group (mean difference (MD) ‐37.4 mL, 95% confidence interval (CI) ‐60.35 to ‐14.45; one study, 39 participants; very‐low certainty evidence). Suprapubic catheterisation versus intermittent self‐catheterisation The studies reported no information on the rate of spontaneous voiding recovery at one week and post‐void residual urine volume at one month following the operation for this comparison. There was no difference in risks of acute complication (risk ratio (RR) 0.77, 95% CI 0.24 to 2.49; one study, 71 participants; very low certainty evidence) and urinary tract infections during the first month after surgery (RR 0.77, 95% CI 0.53 to 1.13; two studies, 95 participants; very‐ low certainty evidence) between participants who underwent suprapubic catheterisation and those who underwent intermittent self‐catheterisation. Available data were insufficient to calculate the relative measures of the effect of interventions on QoL and subjective urinary symptoms. AUTHORS' CONCLUSIONS: None of the included studies reported rate of spontaneous voiding recovery one week after surgery, time to a post‐void residual volume of urine of 50 mL or less, or post‐void residual urine volume at 6 and 12 months after surgery, all of which are important outcomes for assessing postoperative bladder dysfunction. Limited evidence suggested that bethanechol may minimise the risk of bladder dysfunction after radical hysterectomy by lowering post‐void residual urine volume. The certainty of this evidence, however, was very low. The effectiveness of different types of postoperative urinary catheterisation (suprapubic and intermittent self‐catheterisation) remain unproven.